Aspects of Teaching Civilization and Literature in The Algerian High School Case Study: 3rd Year Literary Stream High School - Laghouat - Rebai ,Samia Sabah; Ben Redda , Djamel (Faculty of Letters and Foreign Languages Department of English, 2019)
The present study aims at examining the position of civilization and literature in the Algerian syllable of teaching English in secondary school in the NEW OROSPECTS textbook, third year literature and philosophy in one hand and literature and languages in the other hand. First, it offers an analysis of civilization and literature content of textbook, and deals with the teachers and the students’ questionnaire to ensure more accurate facts. It proposed to investigate teachers and students awareness of the importance of teaching and learning civilization and literature. In addition to assesses the civilization and literature content, to see if it presents enough civilization and literature knowledge or not?. It is concluded that the content of the textbook NEW PROSPECTS is not sufficient to teach literature and civilization because it is considered as a unique source of the two fields. The teachers and the students faced difficulties in both fields. The lack of background knowledge made the students understanding both fields as it is considered a major difficulty facing the students in one hand; and the teachers in the other hand. Both teachers and students are aware of the importance of civilization and literature in this branch